1999
DOI: 10.1007/s004020050377
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of basic fibroblast growth factor on the repair of full-thickness defects in rabbit articular cartilage

Abstract: The effects of exogenous basic fibroblast growth factor (bFGF) on the repair of full-thickness cartilage defects were examined. Four-millimeter diameter, cylindrical defects were made in rabbit articular cartilage and were filled with human recombinant bFGF. The addition of bFGF to the defect induced the formation of a thick cartilage layer composed of chondrocytes and a metachromatic-stained matrix after 6 weeks. The score of the bFGF-treated tissue, as evaluated by a semiquantitative histological scale, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
2
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 15 publications
0
65
2
3
Order By: Relevance
“…Sustained release of bFGF into the joint had therapeutic effects on OA development by the method of controlled-release gelatin hydrogel microspheres (Inoue et al, 2006). Meanwhile, some studies indicated that bFGF could be applied in the treatments for injured cartilage (Cuevas et al, 1988;Fujimoto et al, 1999;Weisser et al, 2001;Yamamoto et al, 2004) and suggested bFGF was potential for repair and regeneration of cartilage defects. Miyakosi et al also reported that bFGF with hyaluronic acid had positive biological effect on osteochondral repair (Miyakosi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained release of bFGF into the joint had therapeutic effects on OA development by the method of controlled-release gelatin hydrogel microspheres (Inoue et al, 2006). Meanwhile, some studies indicated that bFGF could be applied in the treatments for injured cartilage (Cuevas et al, 1988;Fujimoto et al, 1999;Weisser et al, 2001;Yamamoto et al, 2004) and suggested bFGF was potential for repair and regeneration of cartilage defects. Miyakosi et al also reported that bFGF with hyaluronic acid had positive biological effect on osteochondral repair (Miyakosi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively studied in the literature, and found to be involved in numerous cellular functions by binding to and activation of cell-surface receptors in various cell types, including angiogenesis, cell proliferation, wound healing, limb formation, and tissue remodeling (Sorensen et al, 2006). Many studies have implied a potent anabolic effect of bFGF on cartilage homeostasis and suggested its use for cartilage injury and repair (Fujimoto et al, 1999;Nakajima et al, 2007). Moreover, Maniwa et al showed that bFGF could be the more potent chondrocyte mitogen among various growth factors (Kato et al, 1983(Kato et al, , 1985Maniwa et al, 2001), and could stimulate or stabilize the biosynthesis of cartilage matrix components (Yamamoto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, MSCs have been shown to secrete matrix metalloproteinase (MMPs), tissue inhibitor of metalloproteinases (TIMPs), transforming growth factor B-1, and fibroblast growth factor-2 [9][10][11][12]. These molecules have a significant impact on the musculoskeletal system, making the cells ideal candidates for treatment of osteochondral ailments, a major source of permanent disability with nearly 40 million Americans suffering from either osteoporosis or osteoarthritis [13,14].…”
mentioning
confidence: 99%
“…The arrows indicate the area of the graft and host (original magnification ×25) and subchondral bone regenerated within 8 weeks when FGF-2 is directly administered by osmotic pump in a fullthickness articular defect in a rabbit model. Fujimoto et al [3] documented cartilage repair following the administration of a collagen sponge containing 700 ng of FGF-2 in a rabbit model. On the other hand, an overdose of FGF-2 induces hypertrophic arthritis [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Basic fibroblastic growth factor (FGF-2) promotes the repair response in fullthickness articular cartilage defects and bone formation [3,4,6,17,25]. As a carrier material system, the gelatinhydrogel-incorporated growth factor leads to regeneration for cell differentiation and proliferation [24].…”
Section: Introductionmentioning
confidence: 99%